Challenges in mechanics of time dependent materials. Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics. Volume 2 : (2016) - Unknown
No abstract available